Noninvasive prenatal testing, ultrasonographic findings and poor prenatal diagnosis rates for twin pregnancies: a retrospective study - Xiying Yuan; Weinan Wang; Lei Dai; Wenjing Yong; Chenlin Pei; Jingzhi Li; Lingqian Wu (BMC, 2023)
Abstract Background Noninvasive prenatal testing (NIPT) is increasingly used in the clinical prenatal screening of twin pregnancies, and its screening performance for chromosomal abnormalities requires further evaluation. For twin pregnancies with indications for prenatal diagnosis, there is a lack of clinical data to assess the prenatal diagnosis rate (PDR). The aim of this study was to evaluate the screening performance of NIPT for foetal chromosomal abnormalities in twin pregnancies and the PDR in the second and third trimesters. Methods Ultrasound scans were carried out for all twin pregnancies between 11 and 13+ 6 gestational weeks. For twin pregnancies with nuchal translucency thickness˂3.0 mm and no foetal structural malformations, NIPT was performed after blood sampling, followed by routine ultrasound monitoring. Women with twin pregnancies who underwent NIPT at the prenatal diagnostic centre of Xiangya Hospital from January 2018 to May 2022 were included in the study. Genetic counselling was offered to each pregnant woman when the NIPT result indicated a high risk of abnormalities or abnormal ultrasonographic (USG) findings were detected. We followed up twin pregnancies for NIPT results, USG findings, prenatal diagnosis results and pregnancy outcomes. Results In 1754 twin pregnancies, the sensitivity, specificity and positive predictive value of NIPT for trisomy 21 were 100%, 99.9% and 75%, and the corresponding values for sex chromosome aneuploidy (SCA) were 100%, 99.9% and 50%, respectively. For the 14 twin pregnancies for which the NIPT results indicated a high risk of abnormalities, the PDR was 78.6% (11/14). For the 492 twin pregnancies for which the NIPT results indicated a low risk of abnormalities, the rate of USG findings in the second and third trimesters was 39.4% (194/492); of these pregnancies, prenatal diagnosis was recommended for 16.7% (82/492), but it was actually performed in only 8.3% (41/492), and the PDR was 50% (41/82). There was no significant difference in the PDR between the NIPT high-risk and low-risk groups. Conclusions The screening performance of NIPT for SCA in twin pregnancies needs to be further evaluated. When abnormal NIPT results or USG findings are used as the main prenatal diagnostic indicator in the second and third trimesters, the PDR is poor.